Effects of Li+ and Bi3+ substitution on structural, magnetic properties and electroresistance behaviours of La0.8Na0.2MnO3 manganites / Nur Amirah Zahrin - Zahrin, Nur Amirah (2023)
Recent studies in manganites suggested that the changes in resistivity upon the application of higher current, known as the electroresistance (ER) effect is highly influenced by the lattice distortion and the presence of inhomogeneities. However, such effects are not fully understood and require further investigation. Hence, both effects which can be induced by A-site disorder (σ2) and hybridization effect is further investigated in La0.8Na0.2-xLixNa0.2MnO3 (x = 0 – 0.15) and La0.8-xBixNa0.2MnO3 (x = 0 – 0.20) manganites, respectively which was prepared via solid-state method and the structural, magnetic properties and the ER behaviour is determined. For Li-substituted series, the  vs T curve revealed that all samples exhibited a metal-insulator transition behavior and the metal-insulator transition temperature, TMI decreased from 270 K (x=0) to 255 K (x=0.15) with the increase of σ2 from 2.074 x 10-4 Å2 (x=0) to 1.107 x 10-2 Å2 (x=0.15). Both samples of x=0.10 and x=0.15 exhibited ferromagnetic – paramagnetic transition behaviour and a decrease of Curie temperature, TC.